2021
DOI: 10.3390/nano11123429
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Oxygen Reduction Catalysts Derived from the Compounds of High-Specific-Surface-Area Pine Peel Activated Carbon and Phthalocyanine Cobalt

Abstract: Non-platinum carbon-based catalysts have attracted much more attention in recent years because of their low cost and outstanding performance, and are regarded as one of the most promising alternatives to precious metal catalysts. Activated carbon (AC), which has a large specific surface area (SSA), can be used as a carrier or carbon source at the same time. In this work, stable pine peel bio-based materials were used to prepare large-surface-area activated carbon and then compound with cobalt phthalocyanine (C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…Several hypotheses have been proposed and one of the possible degradation pathways is the dissolution of Co ions from the Co−N x active sites during the ORR in acidic media [73] . Recent studies employing hierarchical porous structures for providing high‐specific‐surface‐area have demonstrated to improve the performance and stability of Co−N−C, either in acidic or alkaline electrolytes [75,76] . Another approach to improve electrocatalytic activity and stability is via immobilisation of Co−N 4 moieties in ZIF‐8 micropores, which consists of doping ZIF‐8 with Co using Co−Zn ion exchange followed by pyrolysis.…”
Section: M−n−c (M=fe Co or Ni) Electrocatalysts For The Orrmentioning
confidence: 99%
See 1 more Smart Citation
“…Several hypotheses have been proposed and one of the possible degradation pathways is the dissolution of Co ions from the Co−N x active sites during the ORR in acidic media [73] . Recent studies employing hierarchical porous structures for providing high‐specific‐surface‐area have demonstrated to improve the performance and stability of Co−N−C, either in acidic or alkaline electrolytes [75,76] . Another approach to improve electrocatalytic activity and stability is via immobilisation of Co−N 4 moieties in ZIF‐8 micropores, which consists of doping ZIF‐8 with Co using Co−Zn ion exchange followed by pyrolysis.…”
Section: M−n−c (M=fe Co or Ni) Electrocatalysts For The Orrmentioning
confidence: 99%
“…[73] Recent studies employing hierarchical porous structures for providing high-specific-surface-area have demonstrated to improve the performance and stability of CoÀ NÀ C, either in acidic or alkaline electrolytes. [75,76] Another approach to improve electrocatalytic activity and stability is via immobilisation of CoÀ N 4 moieties in ZIF-8 micropores, which consists of doping ZIF-8 with Co using CoÀ Zn ion exchange followed by pyrolysis. Such an approach enabled a significant increase in the density of CoÀ N x active sites in the SAC-based CoÀ NÀ C structure.…”
Section: Metal Centres Other Than Fementioning
confidence: 99%
“…Co-Pcs. [126] After metal optimization, they found that the catalyst prepared at 800 °C showed the best performance, with an onset potential of 1.006 V, higher than that of the commercial Pt/C (20 wt%) catalyst.…”
Section: Biomass-based Carbon/molecular Catalystsmentioning
confidence: 99%
“…The resulting AC/CoPc composite catalyst exhibited an onset potential of 1.006 V and a stability of 87.8% in 0.1 M KOH, comparable to commercial Pt/C (20%) catalyst. [126] 4.3. Biomass-Based Carbon/Single-Atom Catalysts It should be pointed out that doping is the most common method to load the single-atom sites upon biomass-based carbon supports.…”
Section: Biomass-based Carbon/molecular Catalystsmentioning
confidence: 99%
“…The presence of mixed valences of Co cations in the crystal structure could provide donor–acceptor chemisorption sites for the reversible adsorption of oxygen, thus favouring the ORR process [ 10 , 26 , 27 ]. Moreover, integrating the carbon-based materials with Co 3 O 4 can further improve the relatively high electrocatalytic activity and enhance the durability generated by a synergistic effect between the two components [ 28 , 29 , 30 , 31 , 32 , 33 ]. However, there are only several works which report on the combination of Co 3 O 4 and carbon-based materials via a one-step synthesis method for ORR.…”
Section: Introductionmentioning
confidence: 99%